The Analysis of Pre-Service Physics Teachers in Scientific Literacy: Focus on the Competence and Knowledge Aspects - Pahrudin, A.; Irwandani, I.; Triyana, E.; Oktarisa, Y.; Anwar, C. (Jurnal Pendidikan IPA Indonesia, 2019)
The role of scientific and technological knowledge is needed to compete in the era of industrial revolution 4.0. One of the roles of scientific knowledge is by analyzing the scientific literacy ability of pre-service physics teachers. This research aims to find out how far the achievement of scientific literacy possesses by current pre-service physics teachers. The measurement of scientific literacy encompasses two aspects, namely, competence and knowledge aspects. The subjects of this research were thirty pre-service physics teachers from Universitas Islam Negeri Raden Intan Lampung (State Islamic University Raden Intan Lampung) selected by using purposive sampling. The research instrument used in this research was a test of scientific literacy ability. The data analysis techniques used consisted of data reduction, data display, and verification. The result of the study indicated that some indicators of scientific literacy skills need to be improved. The results showed that there were differences in the achievement of literacy skills in each indicator. In the aspect of competence, the indicator of Indicating Scientific Issues aspects of competence covers identifying issues scientifically (poor), explaining phenomena scientifically (good), using scientific evidence (poor). The aspects of knowledge: content Knowledge (good), procedural knowledge (poor), epistemic knowledge (moderate). Overall the scientific literacy ability of the pre-service physics teachers has not shown satisfying results. It can be concluded that pre-service physics teachers’ literacy ability should be improved. A special strategy is needed that can improve the scientific literacy skills of prospective physics teachers so that the students who will teach in the future also could have good scientific literacy skills.